Beta Thalassemia and Klinefelter syndrome: a rare occurrence - Sushmitha Billapati; G. C. Sowmya; R. S. Tapadia; Usha R. Dutta (Egyptian Journal of Medical Human Genetics, 2022)
Abstract Background β-Thalassemia is an inherited haematological blood disorder in the HBB gene, and variations in this HBB gene lead to the absence/deficiency of the Beta chain synthesis of haemoglobin leading to severe anaemia. Klinefelter syndrome is a chromosomal abnormality that affects physical and cognitive development in males. Affected individuals are taller, show gynaecomastia and behavioural problems and have small testes that do not produce much testosterone. We describe a boy with β-Thalassemia major referred for chromosomal analysis due to delayed puberty and short stature. This is a second case reported in the literature that gives information on two different contradicting genetic disorders in a single individual but novel case as he exhibits additional short-stature phenotype. Case presentation A 17-year-old boy with short stature and gonadal dysfunction was referred for chromosomal analysis. He needed blood transfusion every 4 weeks. The GTG banding for chromosomal analysis and standard PCR for variant detection of HBB gene, Bi-directional Sanger sequencing of the PCR products and multiplex PCR for Y microdeletion of the AZF a, b and c regions on the Y chromosome were performed. The cytogenetic analysis revealed a karyotype of 47,XXY. The HBB gene detected two heterozygous variants forming a pathogenic compound heterozygous condition. The multiplex PCR revealed that the AZF a, b and c regions were intact and were not deleted. Conclusion To our knowledge, this is the second case of a patient with β-Thalassemia associated with Klinefelter syndrome but a novel case with short-stature phenotype association instead of tall stature. The possible association of these two disorders and the unusual phenotypic presentation are discussed. This study highlights the possibility of ruling out Thalassemia while evaluating patients with short stature and delayed puberty.